Immune Checkpoints in Leprosy: Immunotherapy As a Feasible Approach to Control Disease Progression - Lima, Hayana Ramos; Gasparoto, Thaís Helena; de Souza Malaspina, Tatiana Salles; Marques, Vinícius Rizzo; Vicente, Marina Jurado; Marcos, Elaine Camarinha; Souza, Fabiana Corvolo; Nogueira, Maria Renata Sales; Barreto, Jaison Antônio; Garlet, Gustavo Pompermaier; Silva, João Santana da; Brito-de-Souza, Vânia Nieto; et al. (Frontiers in Immunology, 2017)
Leprosy remains a health problem in several countries. Current management of patients with leprosy is complex and requires multi-drug therapy. Nonetheless, antibiotic treatment is insufficient to prevent nerve disabilities and control Mycobacterium leprae. Successful infectious disease treatment demands an understanding of the host immune response against a pathogen. Immune-based therapy is an effective treatment option for malignancies and infectious diseases. A promising therapeutic approach to improve the clinical outcome of malignancies is the blockade of immune checkpoints. Immune checkpoints refer to a wide range of inhibitory or regulatory pathways that are critical for maintaining self-tolerance and modulating the immune response. Programmed cell death protein-1 (PD-1), programmed cell death ligand-1 (PD-L1), CTLA-4 (cytotoxic T-lymphocyte-associated protein 4) and lymphocyte-activation gene-3 (LAG-3) are the most important immune checkpoint molecules. Several pathogens, including M. leprae, are supposed to utilize these mechanisms to evade the host immune response. Regulatory T cells and expression of co-inhibitory molecules on lymphocytes induce specific T-cell anergy/exhaustion, leading to disseminated and progressive disease. From this perspective, we outline how the co-inhibitory molecules PD-1, PD-L1, and Th1/Th17 versus Th2/Treg cells are balanced, how antigen-presenting cell maturation acts at different levels to inhibit T cells and modulate the development of leprosy, and how new interventions interfere with leprosy development.